Age Structure and Neighborhood Homicide: Testing and Extending the Differential Institutional Engagement Hypothesis. (November 2017) - Dollar, Cindy Brooks; McCall, Patricia L.; Land, Kenneth C.; Fink, Joshua
We examine the empirical applicability of differential institutional engagement in explaining the youth age structure effect on neighborhood homicide. Using the National Neighborhood Crime Study and Census data, we conduct a multilevel spatial analysis of homicides in 8, 307 census tracts. We find support for three indicators of differential institutional engagement (disengaged youth, educational engagement, employment engagement). An additional dimension of institutional engagement (familial engagement) operates in the expected direction but is not statistically significant. We argue that previous cross-sectional studies reporting a null or negative relationship between percentage of young and homicide are due to omitting measures of institutional youth (dis)engagement.